THE INFLUENCE OF SELF-CONTROL ON ONLINE SHOPPING BEHAVIOR IN STUDENTS - Amelia; Ladija Mufarika; Mawaddah Ramadhan; Nadia Safana; Rendi Praja Pratama; Faradea Rahmatun; Yesi Anggun Sari (CV. Doki Course and Training, 2023)
This study aims to describe and interpret Influence Self Control on Consumptive Online Shopping Behavior in Semester 4 Student of the Faculty of Psychology UIN Raden Fatah Palembang. The research variables are self control and consumptive consumptive behavior. The behavior. The research population was the 21st batch of students from the Faculty of Psychology, UIN Raden Fatah Palembang. The data collection instrument used a questionnaire to test the hypothesis, the results showed that there was an affect of self control on online shopping behavior in 4th semester student of the Faculty of Psychology UIN Raden Fatah Palembang.